Tuning luminescence of the fluorescent molecule 2-(2-hydroxyphenyl)-1H-benzimidazole via zeolitic imidazolate framework-8. Issue 15 (24th March 2022) - Zhang, Yuyi; Zhang, Wei; Bian, Yajie; Liu, Yiting; Zhang, Xiaolei; Chen, Mengdi; Hu, Bingwen; Jin, Qingyuan
Abstract : ZIF-8 is regarded as a carrier to capture HPBI and eventually the adsorption of the pore structure would saturate, with altering the luminescent intensity. ZIF-8 may be used to sensitively detect nanoscale molecules via changes in fluorescence. Abstract : Zeolitic imidazolate framework-8 (ZIF-8) is one of the most promising metal–organic frameworks because of its excellent high porosity, stability and geometrically well-defined structure. However, the application of ZIF-8 in the field of fluorescent molecular sensing has not been intensively explored. Our work demonstrates the versatility of ZIF-8 as a carrier material, which can be used for small molecule [2-(2-hydroxyphenyl)-1 H -benzimidazole (HPBI)] capture and fluorescence enhancement. ZIF-8 displays luminescent behavior changes when combined with HPBI, as the emission peaks of ZIF-8 and HPBI are located in the same range for resonance enhancement of fluorescence. The results of the experiment indicate that the fluorescence enhancement effect will change in the presence of different concentrations of HPBI. We propose that the pore structure of ZIF-8 could provide an opportunity for the adsorption of HPBI molecules, and eventually the adsorption would saturate. The high porosity of ZIF-8 provides the path to HPBI aggregation or entrance into the ZIF-8 internal structure. Our results suggest that ZIF-8 may offer great promise for molecular fluorescence sensing.